Implications of leading crop production practices on environmental quality and human health - Udeigwe, Theophilus K.; Teboh, Jasper M.; Eze, Peter N.; Hashem Stietiya, M.; Kumar, Vipan; Hendrix, James; Mascagni, Henry J.; Ying, Teng; Kandakji, Tarek (Journal of environmental management, 2015)
Globally, much weight is currently being placed on agriculture to provide food for the growing population as well as feedstock for the bioenergy industry. Unfortunately, the intensification of agricultural operations to satisfy these growing needs has been associated with a number of environmental and human health risks. A review of publications on the subject was conducted and emphasis was placed on articles focusing on agriculture, environment, and public health as well as their interactions. Supporting information was also gathered from publications of various agricultural and environmental agencies. Agricultural practices with potential negative implications on the environment and human health were identified broadly as: (a) utilization of biosolids and animal manures, (b) use of agricultural chemicals, (c) management of post-harvest residue, (d) irrigation, and (e) tillage operations. Soil, water, and air contamination by nutrients, heavy metals, pathogens, and pesticides, as well as air contamination by particulate matters, noxious gases, and pathogens were among the leading environmental impacts. Some of the human-health impacts identified included neurological and reproductive defects, cardiovascular risks, cancers and other diseases (of kidney, liver, lung, and skin), skin allergies, gastroenteritis, and methemoglobinemia. Continual awareness on the impacts of the reviewed agricultural practices on environmental quality and human health and the implementation of experimentally-backed best management practices in agricultural systems remain indispensable. •Principal agricultural practices of environmental concern were discussed.•Leading agricultural contaminants of human health concern were discussed.•Impacts of contaminants on human health were also highlighted.•Findings substantiate the need for more research-based control measures.•Suggestions on best management practices were offered.